Sodium and potassium contents in food samples from the first Portuguese total diet pilot study - Nascimento, Ana (2022)
Eating a varied diet will help ensure an adequate supply of most minerals for healthy people, however excessive sodium (Na) intake leads to an increase in blood pressure, and potassium (K) intake to a balance between the two ions, contributing to the regulation of blood pressure. This work aimed to assess Na and K food sources and evaluate Na:K ratio for the studied food groups. The samples analyzed (n = 169), were selected based on Portuguese food consumption data, and were grouped according to the FoodEx2 level 1 food classification system. Na and K levels were determined using an Induc tively Coupled Plasma Optical Emission Spectrometer. Na contents ranged from 1.20 mg/100 g in bottled water to 2108 mg/100 g in raw cured (or seasoned) meat. The highest content of K (1583 mg/100 g) was found in cod Atlantic. The Na/K ratio was, in general, higher for processed foods. The Portuguese Total Diet Pilot Study (PT TDS), after additional samples are analyzed, could potentially be useful, for evaluating diet-disease risks asso ciated with high Na and low K intake from different foods or food groups.